PELANGGARAN MEREK TERDAFTAR OLEH TOKO BEACH BOY DI DENPASAR (STUDI KASUS PUTUSAN PENGADILAN NEGERI NOMOR : 101/Pid.B/2001/PN.Dps) - Krisnadinatha, A. A. Ngr Gede; Sukihana, Ida Ayu; Darmadha, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Development of the technology at this point is expanded so greatly facilitate theperson in carrying out its work and in its development activities there are manyillegalities that occurred in the community so it is very easy to forge a brand alreadyregistered. One case that occurred in Denpasar is the counterfeiting registeredtrademarks held by beach boy, of an offence the Denpasar District Court hasestablished the award number :101/Pid.B2001/PN.Dps.
Keywords: Infringement, Trademark, Registered